Moscow threatens the balance in the High North: In light of Russia's war in Ukraine, Finland and Sweden are moving closer to NATO - Minna Ålander; Michael Paul (Stiftung Wissenschaft und Politik (SWP), 2022)
Russia's war of aggression against Ukraine is not based on legitimate or reasonable security interests - it is a blatant rejection of Europe's security order. President Vladimir Putin already made this clear in his televised address on 21 February preceding the attack. Previously, Finland and Sweden had recalled the Conference on Security and Cooperation in Europe (CSCE) Final Act of 1975, to which Russia - as the successor state of the Soviet Union - has committed itself. According to the Helsinki Final Act, the sovereign equality of the signatory states is to be respected - and with it their right to choose their alliances freely. Moscow's military aggression not only pushes Helsinki and Stockholm closer to the North Atlantic Treaty Organization (NATO) to an unprecedented extent, but it also makes the containment of Russian power an urgent matter once again. In the long term, it will have implications on the stability in the High North as well.
Keywords: 320